2019
DOI: 10.1029/2019gl085081
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Impacts of Increased Aerosols on Cloud Droplet Number Concentration of Stratus/Stratocumulus and Cumulus

Abstract: In situ aircraft measurements obtained during the RACORO field campaign are analyzed to study the aerosol effects on different cloud regimes. The results show that with increasing cloud condensation nuclei (CCN), cloud droplet number concentration (Nd) significantly increases in stratocumulus (Sc) while remains almost unchanged in cumulus (Cu). By using a new approach to strictly constrain the dynamics in Cu, we found that neither simultaneously changing cloud dynamics nor dilution of cloud water induced by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…In the cross-section of Figure 9b, no decrease in the rain water in the lee side of the Pyrenees is observed, as the cross-section orientation does not include the area characterized by significant rainfall suppression (Figure 8b). The above procedure confirms the fact that cloud and rain water production are two inverse processes [106,107], highly dependent on the impact of the CCN to the atmospheric conditions.…”
Section: Impact On the Precipitation Patternsupporting
confidence: 77%
See 1 more Smart Citation
“…In the cross-section of Figure 9b, no decrease in the rain water in the lee side of the Pyrenees is observed, as the cross-section orientation does not include the area characterized by significant rainfall suppression (Figure 8b). The above procedure confirms the fact that cloud and rain water production are two inverse processes [106,107], highly dependent on the impact of the CCN to the atmospheric conditions.…”
Section: Impact On the Precipitation Patternsupporting
confidence: 77%
“…Apart from the enhanced evaporation, high amounts of relative humidity contribute to the above mechanism. On the contrary, pristine conditions lead to the exact opposite results, as limited evaporation conditions, lower relative humidity amounts and decreased cloud water mixing ratios lead to important cloud to rain water conversion and enhancement of precipitation [106,107]. It is remarkable that the prognostic treatment of dust particles enhances significantly the precipitation over areas far away from the dust event.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the Southern Oceans only has a limited impact on the global-averaged RF aci due to its low anthropogenic fraction 35 . In situ observations have demonstrated that the response of N d to aerosols is more sensitive for stratiform clouds than cumuliform clouds 26 . Also, stratiform ones have smaller retrieval biases for the N d retrieval than cumulus ones 16 , thus suffer less AIE underestimation caused by partly cloudy retrievals 17,25 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the marine boundary layer is deeper and more likely to be decoupled in this region, so the aerosols and precursor gases emitted by ships near the surface may not be efficiently transported to the subcloud layer. Additionally, it is possible that cumuliform clouds are less susceptible to aerosol‐driven increased in N d than stratiform clouds for physical reasons, such as differences in supersaturation adjustments between the two regimes (Jia et al, ).…”
Section: The Issue Of Detectability and Its Policy Implicationsmentioning
confidence: 99%